"Ahead" to Basics - Schwerin, Ursula ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
With a view toward the future, this paper raises and begins to answer the following four questions about education in tomorrow's world. First, will the "basics" as presently defined continue to be the basics, and if so, is society ready to support them? Second, are there new basics which must be integrated into school curricula, and, if so, what are they? Third, how can citizens be certain that ever increasing bodies of knowledge can be made available to the curious minds of children? Fourth, are Americans ready to commit themselves through concerted action to the principle that education is a basic human right? The article ends with the open question: Are Americans, as a nation, ready to pay the price for excellence that the future demands? (RH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Education; Basic Skills; Educational Change; Elementary Secondary Education; Equal Education; Futures (of Society); Opinion Papers